P.034 Focal cortical dysplasia type IIIb associated with oligodendroglioma in a seizure free patient: a case report. (2nd June 2017) - MacLean, MA; Easton, AS; Pickett, GE
Abstract : Background: Focal cortical dysplasia (FCD) refers to malformation of cortical development featuring abnormalities of cortical layering, neuronal differentiation and maturation. It is a common cause of medically refractory epilepsy. The coexistence of FCD and low-grade glial neoplasms such as ganglioglioma and dysembryoplastic neuroepithelial tumour is classified by the International League Against Epilepsy as "FCD Type IIIb". We present a case of FCD Type IIIb associated with low grade oligodendroglioma (WHO grade II) in a seizure free patient.Methods: A 20-year-old male presented with suspected arteriovenous malformation of the right pinna. Imaging revealed an incidental right frontal lobe mass. Surgical resection was performed. Pathologic analysis revealed FCD Type IIIb associated with low grade oligodendroglioma (WHO grade II).Results: The patient recovered uneventfully. Only 4 prior cases of FCD Type IIIb associated with oligodendroglioma have been reported. This is the first reported case of FCD Type IIIb discovered incidentally in a seizure free patient.Conclusions: FCD Type IIIb associated with oligodendroglioma is rare. The mechanism(s) by which glioneuronal neoplasms and perilesional cortical tissue jointly contribute to epileptogenicity have not been clearly defined. There may be a reduced risk of seizures with oligodendroglioma rather than tumors with a neuronal component.